Morphological Spectrum Of Vascular Neoplasms: A Histopathological Study In A Tertiary Care Center In South India - Phalak, Pooja Ashok; Jojo, Annie (Annals of Pathology and Laboratory Medicine, 2023)
Background Vascular neoplasms can be benign asymptomatic, locally aggressive, or highly malignant. It is important to subclassify them as it strongly influences the treatment and prognosis. However, only a few case series are published now. Hence in this study, we aim to classify vascular neoplasms into various categories and to find their relationship with age, sex, and location. Methods A retrospective analysis of vascular neoplasms from 2013-2018 in the department of pathology at Amrita Institute of Medical Sciences (AIMS), Kochi was done. Results A total of 221 vascular neoplasms were identified and were subclassified into benign-186(84.2%), intermediate-4(1.8%), and malignant-31(14%) according to World Health Organization (WHO) classification. The majority of the benign tumors were various types of hemangiomas-153(82.2%) and were common in young adult females. The commonest site of occurrence was head and neck, followed by soft tissue. The majority of malignant neoplasms were angiosarcomas-26(84%) and were more common in elderly females. Skin and soft tissue, followed by breast were the frequently involved sites. The second malignant neoplasm was epithelioid hemangioendothelioma-5(16%) which was common in the head and neck. Other rare types of hemangioendothelioma were included in the intermediate category. Conclusion The commonest benign vascular tumor is hemangioma, which occurs mostly in adult females in the head and neck region. The commonest malignant vascular tumor is angiosarcoma which occurs in elderly females in the skin and soft tissue and has a poor prognosis